Votive body parts in Greek and Roman religion - Hughes, Jessica (Cambridge classical studies, 2017)
This book examines a type of object that was widespread and very popular in classical antiquity - votive offerings in the shape of parts of the human body. It collects examples from four principal areas and time periods: Classical Greece, pre-Roman Italy, Roman Gaul and Roman Asia Minor. It uses a compare-and-contrast methodology to highlight differences between these sets of votives, exploring the implications for our understandings of how beliefs about the body changed across classical antiquity. The book also looks at how far these ancient beliefs overlap with, or differ from, modern ideas about the body and its physical and conceptual boundaries. Central themes of the book include illness and healing, bodily fragmentation, human-animal hybridity, transmission and reception of traditions, and the mechanics of personal transformation in religious rituals.